The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15050982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Factors Associated with Fear of Falling between Older Adults with and without a Fall History

Abstract: Background: Although fear of falling (FOF) has been studied since FOF has negative consequences for the elderly, there is limited information about the risk factors of FOF, including the environment. The purpose of this study was to describe individual and environmental factors of FOF between those with and without a fall history from an ecological aspect and to examine whether individual and environmental factors differently affect the FOF according to the state of fall history in community-dwelling older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 39 publications
7
55
1
6
Order By: Relevance
“…To our knowledge, this is the first study to compare the prevalence and factors of FOF among community‐dwelling older adults from Latin America and Europe. Consistent with previous findings (Lavedan et al, ; Lee, Oh, & Hong, ; Makino et al, ), the average score for FOF was extremely high in three‐quarters of the studied sample. However, high FOF was much more prevalent among Portuguese participants.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to compare the prevalence and factors of FOF among community‐dwelling older adults from Latin America and Europe. Consistent with previous findings (Lavedan et al, ; Lee, Oh, & Hong, ; Makino et al, ), the average score for FOF was extremely high in three‐quarters of the studied sample. However, high FOF was much more prevalent among Portuguese participants.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, the cause and effect relationship between falls and arthritis could be unknown, which was an inherent limitation of this design. Third, to simplify our hypothesis, we did not take into account environmental variables (such as residential area, housing type, and so on), which were considered in other FOF studies [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Vietnamese elderly are exposed to less social interactions due to the limited social activities held by the local authority as compared to other developed countries [6]. Elderly with lower levels of social support are more likely to be physically inactive [38], depressed [36,39,40], which are reported to be closely related to FoF [18,41]. In addition, we found that the mean MMSE score of the participants with low-moderate perceived social support levels was 25.5, which was significantly lower than that of those with a high perceived level of social support (26.6) (Appendix table 2).…”
Section: Cognitive Impairment and Fof Among Different Perceived Sociamentioning
confidence: 99%